Development of "pre-mix method" for mixing steel fiber reinforced concrete with new mixing technology - Gyawali, Tek Raj (Journal of Science and Engineering, 2014)
When mixing Steel Fiber Reinforced Concrete (SFRC) in conventional mixers, there is limitation of fiber percentage (maximum up to 2.5%). And, when mixing in newly developed Energy Saving Gravity (ESG) continuous mixer with conventional mixing method, good quality of SFRC could not be obtained due to blockage problem even for low percentage of fibers when mixing continuously. In order to overcome both of above mentioned problem, new mixing method called “Pre-mix Method” is developed. This paper outlines the mechanism of new mixing technology and application of pre-mix method for mixing SFRC. It is verified that the use of this method has prevailed to make possible of SFRC with increase of fiber percentage up to 4% in new continuous mixer.